Waterproof super high-toughness building structural adhesive and preparation method thereof
Patent Information
- Application Number
- CN202611216547.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-13
AI Technical Summary
1.韧性不足,易脆性破坏
1.本发明通过有机硅增韧剂开环后原位插入环氧树脂分子链段,构建"刚性链段-柔性链段"三维互穿网络,使固化后的胶体从脆性断裂模式转变为韧性断裂模式,显著提高拉伸剪切强度和抗冲击性能,满足植筋、粘钢、预制拼接、封缝等受力场景的要求;
Smart Images

Figure CN122898236A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building adhesive technology, and more specifically, to a water-resistant, ultra-high toughness structural adhesive for buildings and its preparation method. Background Technology
[0002] Structural adhesives are core chemical building materials for concrete infrastructure construction, reinforcement, renovation, and prefabrication. They mainly include rebar adhesives, precast component splicing adhesives, steel bonding adhesives, joint sealing adhesives, and fiber bonding adhesives, and are widely used in highways, railways, bridges, tunnels, waterway terminals, wind turbine towers, prefabricated buildings, and residential building renovations. Mainstream products use a two-component epoxy resin system as the matrix, combined with inorganic fillers such as silica powder and glass powder, as well as curing agents and additives. They are used for connecting new and old concrete, anchoring rebar, splicing precast segments, steel bonding reinforcement, crack sealing, and grouting.
[0003] However, existing structural adhesives for buildings have the following problems: 1. Insufficient toughness, prone to brittle fracture. Ordinary epoxy resin becomes hard and brittle after curing, with low tensile and shear strength. It is prone to brittle fracture under load and is likely to fail in stress scenarios such as dynamic loads on bridges, splicing of precast components, and anchoring of rebar.
[0004] 2. Poor adhesion performance, unreliable application on wet surfaces. Most products cannot be stably cured in humid / underwater environments, have limited wetting and penetration depth at the concrete interface, resulting in a large difference in dry / wet bond strength, and easy debonding on damp substrates.
[0005] 3. Poor thixotropy and storage stability. High filler content combined with an inefficient thixotropic system makes it prone to stratification and sedimentation during long-term storage; traditional non-vacuum packaging processes in drums easily introduce air bubbles, affecting the density and mechanical properties of the colloid.
[0006] 4. Poor workability. Construction on facades, ceilings, and slopes is prone to dripping, limiting its applicability to various scenarios and failing to simultaneously meet the common requirements of multiple scenarios such as rebar installation, splicing, steel bonding, and joint sealing.
[0007] 5. Insufficient durability. Its resistance to damp heat aging, media, and fatigue is average. Its strength decreases significantly with long-term use, making it difficult to meet the long-life requirements of major projects.
[0008] Therefore, those skilled in the art are dedicated to providing a water-resistant, ultra-high toughness structural adhesive for building structures that can effectively solve the above-mentioned technical problems and its preparation method. Summary of the Invention
[0009] According to a first aspect of the embodiments of this specification, a water-resistant, ultra-high toughness structural adhesive is provided. The structural adhesive is a two-component system, including component A and component B. Component A includes an in-situ grafted toughened epoxy resin with organosilicon and surface-modified microsilica powder with GPTMS. Component B includes a biomimetic group grafted modified amine curing agent. The mass ratio of component A to component B is 2:1 to 4:1.
[0010] In one possible implementation, the in-situ grafted toughened epoxy resin is prepared by in-situ grafting of epoxy resin and silicone toughening agent, wherein the silicone toughening agent is inserted in-situ into epoxy resin molecular chain segments to construct a three-dimensional interpenetrating network of rigid and flexible segments. The GPTMS surface-modified microsilica powder is prepared by grafting microsilica powder onto the GPTMS surface. The GPTMS introduces epoxy and hydroxyl groups on the surface of the microsilica powder, enabling covalent bonding between the microsilica powder, the epoxy matrix, and the curing agent. The biomimetic group grafted modified amine curing agent is prepared by grafting a modified amine curing agent and a biomimetic group modifier. The biomimetic group modifier mimics the active groups in marine biological adhesion proteins, covalently grafting biomimetic molecules containing amino or hydroxyl groups onto the epoxy backbone or side chains through a ring-opening reaction. This allows the curing agent to form hydrogen bonds, coordination bonds, and chemical crosslinks in humid or underwater environments, achieving efficient adhesion on wet surfaces and stable underwater curing.
[0011] In one possible implementation, the organosilicon toughening agent is made from 1,3-bis[3-(2,3-epoxypropoxy)-propyl]-1,1,3,3-tetramethyldisiloxane and dimethylcyclosiloxane.
[0012] In one possible implementation, the epoxy resin is a bisphenol A type epoxy resin; the modified amine curing agent is at least one of modified cycloaliphatic amine and polyether amine curing agent.
[0013] In one possible implementation, component A further includes refined silica powder, glass powder, fumed silica thixotropic agent, defoamer, and silane coupling agent; and component B further includes accelerator and rheology modifier.
[0014] In one possible implementation, by weight, component A comprises: 100 parts of bisphenol A type epoxy resin, 8-12 parts of organosilicon toughening agent, 15-25 parts of GPTMS surface-modified microsilica powder, 30-45 parts of refined silica powder, 10-20 parts of glass powder, and 3-6 parts of fumed silica thixotropic agent; and component B comprises: 40-55 parts of modified amine curing agent, 5-10 parts of biomimetic group modifier, and 1-2 parts of accelerator.
[0015] According to a second aspect of the embodiments of this specification, a method for preparing a water-resistant, ultra-high toughness structural adhesive is provided, comprising the following steps: Step 1: Mix epoxy resin with organosilicon toughening agent and react to obtain organosilicon in-situ grafted toughened epoxy resin. Step 2: Surface grafting modification treatment of microsilica powder and GPTMS is carried out to obtain GPTMS surface-modified microsilica powder; Step 3: Mix the in-situ grafted toughened epoxy resin obtained in Step 1 with the surface-modified microsilica powder of GPTMS obtained in Step 2 and other additives, and then perform vacuum degassing treatment to obtain Component A. Step 4: The modified amine curing agent and the biomimetic group modifier are mixed and reacted to obtain the biomimetic group grafted modified amine curing agent. Then, the additives are added and the mixture is subjected to vacuum stirring to obtain component B. Step 5: Vacuum fill the components A obtained in Step 3 and B obtained in Step 4 into dual-tube dispensers or drums, respectively, and use a static mixer. The mass ratio of component A to component B is 2:1 to 4:1.
[0016] In one possible implementation, in step 1, the temperature of the mixing reaction is 60-80°C, and the reaction is maintained at this temperature for 2-4 hours.
[0017] In one possible implementation, in step 3, after cooling to ≤60℃, refined silicon micro powder, glass powder and fumed silica thixotropic agent are added, and dispersed at high speed for 1-2 hours under vacuum conditions of -0.09~-0.1MPa. Then, defoamer and silane coupling agent are added, and the mixture is stirred under vacuum for 30-60 minutes to obtain component A.
[0018] In one possible implementation, in step 4, the temperature of the mixing reaction is 40-50°C, the reaction is kept at this temperature for 1-2 hours, and then an accelerator and a rheology modifier are added, followed by vacuum stirring for 30-60 minutes to obtain component B.
[0019] As described above, the present invention provides a water-resistant, ultra-high toughness structural adhesive for buildings and its preparation method, which has the following beneficial effects: 1. This invention constructs a three-dimensional interpenetrating network of "rigid segments-flexible segments" by in-situ insertion of an organosilicon toughening agent into epoxy resin molecular chain segments after ring opening, which transforms the cured colloid from a brittle fracture mode to a ductile fracture mode, significantly improving tensile shear strength and impact resistance, and meeting the requirements of stress scenarios such as rebar installation, steel bonding, prefabricated splicing, and joint sealing. 2. This invention utilizes GPTMS to surface-graft and modify microsilica powder, introducing epoxy and hydroxyl groups to strengthen interfacial bonding. Simultaneously, the curing agent grafts biomimetic functional groups to form hydrogen bonds, coordination bonds, and chemical crosslinks in humid / underwater environments, achieving highly efficient wet bonding and stable underwater curing. This significantly improves wet bonding strength and interfacial anchoring force, enabling reliable construction in dry, humid, and underwater environments. Specifically, it includes: 1) After GPTMS ring-opening, the epoxy groups react with the hydroxyl groups on the surface of the silica powder to form covalent bonds; 2) The epoxy groups on the surface of the modified silica powder react with the amine groups of the curing agent to form interfacial chemical crosslinks; 3) The covalent bonding and chemical crosslinking mentioned above synergistically enhance the toughness and strength of the structural adhesive; 3. This invention utilizes the silanol groups of fumed silica thixotropic agents to form a reversible hydrogen bond network, achieving static high viscosity to prevent sedimentation and shear thinning for easy construction. Combined with vacuum negative pressure high-speed stirring and vacuum filling processes, it eliminates air bubbles, ensures uniform dispersion of fillers, improves colloidal density and long-term storage stability, and prevents stratification and sedimentation during long-term storage. 4. This invention endows the colloid with thixotropic and controllable properties through a reversible hydrogen bond network. It thins under shear for easy construction and recovers high consistency when stationary. It does not flow when applied to vertical, inclined, or top surfaces. One formula can be directly adapted to the general requirements of multiple scenarios such as rebar adhesive, precast splicing adhesive, steel bonding adhesive, sealing adhesive, and fiber bonding adhesive. 5. This invention improves the resistance to damp heat aging, heat aging, acid and alkali, and salt spray by in-situ grafting toughening with organosilicon and forming π-π stacking and chemical bonding at the interface with modified fillers and epoxy matrix. It also has a low strength decay rate, meeting the long-term use requirements of harsh environments such as bridges, tunnels, and docks. Attached Figure Description
[0020] Figure 1 This is a flowchart illustrating a method for preparing a water-resistant, ultra-high toughness structural adhesive for buildings provided by the present invention. Detailed Implementation
[0021] The present invention will be further described below with reference to the accompanying drawings and embodiments: In the description of this invention, it should be noted that "parts" refers to parts by mass; the endpoints of the content range of each component are included, for example, "8-12 parts" means greater than or equal to 8 parts and less than or equal to 12 parts. The process parameters such as temperature, pressure, and time described in this invention are typical process conditions during implementation. Those skilled in the art can adjust them within a reasonable range according to actual conditions without departing from the protection scope of this invention. The terms "comprising" or "including" used in this invention are open-ended, meaning that in addition to the listed components or steps, other unlisted components or steps may also be included. The vacuum conditions described in this invention refer to a negative pressure environment below atmospheric pressure; the specific vacuum degree is based on the listed values.
[0022] This invention discloses a water-resistant, ultra-high toughness structural adhesive and its preparation method. The adhesive is a two-component system. Component A comprises an organosilicon in-situ grafted toughened epoxy resin, GPTMS surface-modified microsilica powder, and additives. Component B comprises a biomimetic group-grafted modified amine curing agent and additives. The preparation method includes: preparing the organosilicon grafted toughened epoxy resin; surface-grafting modification of the microsilica powder; synthesizing the biomimetic group-modified amine curing agent; mixing the components separately to obtain components A and B; and finally, mixing and vacuum degassing to obtain the finished product. This invention, through a combination of molecular design and process, enables the product to maintain high strength while possessing ultra-high toughness, excellent adhesion to dry and wet surfaces and underwater, good storage stability, and anti-flow properties on facades. It is suitable for the reinforcement and repair of building structures in harsh environments such as dampness and underwater.
[0023] The technical problems to be solved by this invention include: overcoming the bottleneck of brittle epoxy resin to achieve high strength, high toughness, and impact resistance, meeting the stress requirements of rebar installation, steel bonding, prefabrication, and sealing; achieving stable curing in dry / humid / underwater environments, significantly improving wet bonding strength and interface anchoring force; constructing an excellent thixotropic system to achieve long-term storage without delamination, construction without flow, and colloid without air bubbles; and improving durability properties such as water resistance, resistance to damp heat aging, and resistance to media, meeting the long-term use requirements of harsh environments such as bridges, tunnels, and docks.
[0024] The technical solution of this invention takes in-situ toughening of epoxy resin as the core, combined with filler surface modification, biomimetic group grafting, thixotropic system optimization and vacuum negative pressure preparation process, to prepare a two-component water-resistant high-toughness building structural adhesive, and simultaneously solves the problems of toughness, wet bonding, storage stability and durability.
[0025] The product composition of this invention is as follows: Component A (base adhesive) includes in-situ grafted toughened epoxy resin with organosilicon, surface-modified microsilica powder of GPTMS, refined quartz silica powder (refined silica powder), glass powder, thixotropic agent, defoamer, and coupling agent; Component B (curing agent) includes modified amine curing agent, biomimetic group grafting modifier, accelerator, and rheology modifier. The mass ratio of component A to component B is 2:1 to 4:1.
[0026] The key technologies of this invention include the following three aspects: Key Technology 1: In-situ grafting toughening of organosilicon + epoxy-filler composite high-strength system. Organosilicon molecules are inserted in situ into epoxy molecular chains to construct a three-dimensional interpenetrating network of "rigid segments-flexible segments", realizing the transformation from brittle fracture to ductile fracture; the modified filler and epoxy form an interfacial π-π stacking and chemical bonding, improving the overall strength, toughness, fatigue resistance and durability.
[0027] Key Technology 2: GPTMS filler surface modification + biomimetic group grafting. Microsilica powder is surface modified with GPTMS to introduce epoxy and hydroxyl groups, which form covalent bonds with epoxy and curing agent to strengthen interfacial bonding; the curing agent is grafted with biomimetic functional groups to form hydrogen bonds, coordination bonds and chemical crosslinking in humid / underwater environments, achieving efficient adhesion on wet surfaces and underwater curing.
[0028] Key Technology 3: Thixotropic System Optimization + Vacuum Negative Pressure Preparation Process. The thixotropic agent forms a reversible hydrogen bond network through silanol groups (Si-OH), exhibiting high viscosity at rest to prevent sedimentation, and thinning under shear for easy application, without dripping on vertical surfaces; high-speed stirring under vacuum negative pressure + vacuum filling eliminates air bubbles, ensures uniform dispersion of fillers, and creates a dense colloid, improving stability and mechanical properties.
[0029] Example 1 This embodiment provides a water-resistant, ultra-high toughness structural adhesive for buildings. The adhesive is a two-component system, comprising component A and component B. Component A includes an in-situ grafted toughened epoxy resin with organosilicon and GPTMS (dimethyldihydroxypropyltrimethoxysilane CAS: 2530-83-8, KH-560) surface-modified microsilica powder (CAS: 69012-64-2, SiO2 content ≥92%, specific surface area 18000 m²). 2 / kg), wherein component B includes a biomimetic group grafted modified amine curing agent, and the mass ratio of component A to component B is 2:1 to 4:1.
[0030] Therefore, the structural adhesive in this embodiment adopts a two-component system. In component A, the organosilicon in-situ grafted toughened epoxy resin constructs a three-dimensional interpenetrating network of "rigid segments-flexible segments" by inserting organosilicon molecules in situ into epoxy molecular chains, achieving the transformation from brittle fracture to ductile fracture. In component A, the GPTMS surface-modified microsilica powder introduces epoxy and hydroxyl groups after GPTMS surface modification, forming covalent bonds with epoxy and curing agent to strengthen interfacial bonding. In component B, the biomimetic group grafted modified amine curing agent grafts biomimetic functional groups, forming hydrogen bonds, coordination bonds, and chemical crosslinks in humid / underwater environments, achieving efficient wet surface adhesion and underwater curing. Through the synergistic combination of the above-mentioned necessary technical features, this embodiment can simultaneously solve the problems of insufficient toughness, poor wet adhesion, and poor storage stability.
[0031] Example 2 This embodiment, based on Example 1, further explains the composition of the in-situ grafted toughened epoxy resin with organosilicon, the surface-modified microsilica powder of GPTMS, and the biomimetic group (L-DOPA) grafted modified amine curing agent.
[0032] The organosilicon in-situ grafted toughening epoxy resin is prepared by in-situ grafting of epoxy resin and organosilicon toughening agent. The organosilicon toughening agent is prepared from 1,3-bis[3-(2,3-epoxypropoxy)-propyl]-1,1,3,3-tetramethyldisiloxane (CAS: 126-80-7) and dimethylcyclosiloxane (CAS: 68037-71-8). A ring-opening rearrangement reaction is carried out under the catalysis of tetramethylammonium hydroxide (TMAH, CAS: 75-59-2, 25wt% aqueous solution), and the reaction formula is as follows:
[0033] In the above reaction, the epoxy groups at both ends of the tetramethyldisiloxane (DOTMDS) molecular chain recombine with the open-ring segments of dimethylcyclosiloxane (Dn) through siloxane bonds to generate modified siloxane products (n=3,4,5,6) with epoxy groups at both ends and flexible siloxane segments in the middle. This modified siloxane is inserted in situ into the epoxy resin molecular chain segment to construct a three-dimensional interpenetrating network of "rigid segments-flexible segments", which transforms the cured colloid from a brittle fracture mode to a ductile fracture mode, significantly improving its impact resistance.
[0034] The GPTMS-modified microsilica powder is prepared by grafting microsilica (silica fume, CAS: 69012-64-2, SiO2 content ≥92%, specific surface area 18000 m² / kg) onto the surface of GPTMS. The GPTMS is γ-glycidyl etheroxypropyltrimethoxysilane (CAS: 2530-83-8). GPTMS introduces epoxy and hydroxyl groups onto the surface of the microsilica powder, enabling covalent bonding between the microsilica powder, the epoxy matrix, and the curing agent, strengthening the filler-matrix interface and improving overall strength and durability.
[0035] The biomimetic group-grafted modified amine curing agent is prepared by grafting a modified amine curing agent and a biomimetic group modifier. The biomimetic group modifier introduces biomimetic functional groups onto the modified amine curing agent molecule. These biomimetic functional groups mimic the active groups found in marine bioadhesion proteins (L-DOPA, CAS: 59-92-7). These functional groups are covalently grafted onto the curing agent molecular chain via a ring-opening reaction of biomimetic molecules containing amino or hydroxyl groups (such as dopamine derivatives). This allows the curing agent to form hydrogen bonds, coordination bonds, and chemical crosslinks in humid or underwater environments. The epoxy groups provide a rigid network and cohesive strength, while the biomimetic functional groups provide interfacial adhesion and energy dissipation mechanisms, achieving efficient adhesion on wet surfaces and stable underwater curing.
[0036] Example 3 This embodiment, based on Example 2, further explains the specific types of epoxy resin and modified amine curing agent.
[0037] The epoxy resin is a bisphenol A type epoxy resin, specifically a liquid low-molecular-weight bisphenol A diglycidyl ether mixture (CAS: 61788-97-4), E51 type epoxy resin, with an epoxy value of 0.48–0.54 eq / 100g, an epoxy equivalent of 184–200 g / eq, and a rotational viscosity of 8000–15000 mPa·s at 25°C. Bisphenol A type epoxy resin possesses excellent adhesive properties and mechanical strength, making it the most commonly used matrix resin in the field of structural adhesives for construction. When grafted in situ with an organosilicon toughening agent, it can achieve a significant toughening effect while maintaining high strength.
[0038] The modified amine curing agent is at least one of a modified alicyclic amine (5-amino-1,3,3-trimethylcyclohexylamine IPDA, CAS: 2855-13-2) and a polyether amine (O,O'-bis(2-aminopropyl)polypropylene glycol, amino-terminated polyether, CAS: 9046-10-0) curing agent. The modified alicyclic amine curing agent has low viscosity, good weather resistance, and water resistance; the polyether amine curing agent has good flexibility and high adhesive strength; the combination of the two can achieve stable curing in humid environments.
[0039] Example 4 This embodiment, based on Embodiment 3, further explains the remaining components in Component A and Component B.
[0040] Component A further includes refined silica powder, glass powder (sodium-calcium silicate glass powder, CAS: 65997-17-3, particle size 800-3000 mesh), fumed silica thixotropic agent (CAS: 112945-52-5), defoamer, and silane coupling agent. The refined silica powder and glass powder act as fillers, improving the density and mechanical properties of the colloid. The fumed silica thixotropic agent (CAS: 112945-52-5) forms a reversible hydrogen bond network through silanol groups (Si-OH), achieving static high viscosity to prevent settling, shear thinning for easy construction, and no dripping on vertical surfaces. The defoamer (ordinary polydimethylsiloxane, i.e., dimethyl silicone oil PDMS, CAS: 9006-65-9) eliminates bubbles generated during mixing. The silane coupling agent (γ-glycidyl etheroxypropyltrimethoxysilane, CAS: 2530-83-8) further enhances the interfacial bonding between the filler and the epoxy matrix.
[0041] Component B also includes an accelerator and a rheology modifier. The accelerator accelerates the curing reaction process and shortens the construction waiting time; the rheology modifier adjusts the rheological properties of component B to ensure the workability and anti-flow properties of the facade after mixing components A and B.
[0042] Example 5 This embodiment further explains the specific mass ratio of each component based on embodiment 4.
[0043] By weight, component A comprises: 100 parts bisphenol A epoxy resin, 8-12 parts organosilicon toughening agent, 15-25 parts GPTMS surface-modified microsilica powder, 30-45 parts refined silica powder, 10-20 parts glass powder, and 3-6 parts fumed silica thixotropic agent. Component B comprises: 40-55 parts modified amine curing agent, 5-10 parts biomimetic group modifier, and 1-2 parts accelerator.
[0044] As an example, when 100 parts of bisphenol A type epoxy resin E51 are in component A, 10 parts of organosilicon toughening agent, 20 parts of GPTMS surface-modified microsilica powder, 38 parts of refined silica powder, 15 parts of glass powder, and 4 parts of fumed silica thixotropic agent are used; in component B, 48 parts of modified amine curing agent, 8 parts of biomimetic group modifier, and 1.5 parts of accelerator are used. Defoamer, silane coupling agent, and rheology modifier are added in appropriate amounts.
[0045] Therefore, it can be seen that within the above-mentioned ratio range, the components work synergistically to enable the structural adhesive to maintain high strength while possessing ultra-high toughness and excellent wet bonding performance.
[0046] In summary, this invention provides a water-resistant, ultra-high toughness structural adhesive for buildings. The adhesive is a two-component system, comprising component A and component B, with a mass ratio of component A to component B of 2:1 to 4:1. Component A comprises: 100 parts of bisphenol A type epoxy resin, 8-12 parts of organosilicon toughening agent, 15-25 parts of GPTMS surface-modified microsilica powder, 30-45 parts of refined silica powder, 10-20 parts of glass powder, 3-6 parts of fumed silica thixotropic agent, and appropriate amounts of defoamer and silane coupling agent. Component B comprises: 40-55 parts of at least one of modified cycloaliphatic amine and polyetheramine curing agent, 5-10 parts of biomimetic group modifier, 1-2 parts of accelerator, and appropriate amounts of rheology modifier. Among them, the organosilicon in-situ grafted toughening epoxy resin is prepared by in-situ grafting reaction of bisphenol A type epoxy resin and organosilicon toughening agent; the GPTMS surface-modified microsilica powder is prepared by grafting modification of microsilica powder onto the surface of GPTMS; and the biomimetic group grafted modified amine curing agent is prepared by grafting reaction of modified amine curing agent and biomimetic group modifier.
[0047] Example 6 like Figure 1 As shown, this embodiment provides a method for preparing a water-resistant, ultra-high toughness structural adhesive as described in Example 1, comprising the following steps: Step 1: Mix epoxy resin with organosilicon toughening agent to prepare organosilicon in-situ grafted toughened epoxy resin.
[0048] Specifically, after heating the epoxy resin, an organosilicon toughening agent is added, and the reaction is carried out under heat preservation. The organosilicon molecules are inserted in situ into the epoxy molecular chain segments to construct a three-dimensional interpenetrating network of "rigid chain segments-flexible chain segments", thus completing the in-situ grafting toughening.
[0049] Step 2: Surface grafting modification of microsilica powder with GPTMS is performed to obtain GPTMS surface-modified microsilica powder.
[0050] Specifically, by grafting GPTMS onto the surface of silica powder, epoxy groups and hydroxyl groups are introduced, enabling covalent bonds to be formed between the silica powder, epoxy matrix, and curing agent, thereby strengthening the interfacial bonding.
[0051] Step 3: Mix the in-situ grafted toughened epoxy resin obtained in Step 1 with the surface-modified microsilica powder of GPTMS obtained in Step 2 and other additives, and then perform vacuum degassing treatment to obtain Component A. Step 4: The modified amine curing agent and the biomimetic group modifier are mixed and reacted to obtain the biomimetic group grafted modified amine curing agent. Then, the additives are added and the mixture is subjected to vacuum stirring to obtain component B. Specifically, the biomimetic group modifier introduces biomimetic functional groups into the modified amine curing agent molecule, enabling it to form hydrogen bonds, coordination bonds and chemical crosslinks in humid or underwater environments, thereby achieving efficient adhesion on wet surfaces and stable underwater curing.
[0052] Step 5: Vacuum fill the components A obtained in Step 3 and B obtained in Step 4 into dual-tube dispensers or drums, respectively, and use a static mixer. The mass ratio of component A to component B is 2:1 to 4:1.
[0053] Therefore, the preparation method of this embodiment involves preparing toughened epoxy resin and modified microsilica powder in steps 1 and 2 respectively, which are then combined in step 3 to form component A. Component B is obtained by preparing a biomimetic group-grafted modified amine curing agent in step 4. Finally, in step 5, component A and component B are mixed in a specific ratio to obtain a water-resistant, ultra-high toughness structural adhesive. Each step is connected in series via material flow, with the product of the previous step serving as the processing target for the next, ensuring the continuity of the preparation process and the consistency of the product's performance.
[0054] Example 7 This embodiment further explains the process parameters of step 1 based on embodiment 6.
[0055] In step 1, the temperature of the mixing reaction is 60-80℃, and the reaction is maintained at this temperature for 2-4 hours.
[0056] As an example, bisphenol A type epoxy resin E51 was heated to 70°C, an organosilicon toughening agent was added, and the reaction was maintained at the temperature for 3 hours to complete the in-situ grafting toughening.
[0057] Therefore, within a temperature range of 60-80℃, the organosilicon toughening agent can fully insert into the epoxy molecular chain segment to complete in-situ grafting. Maintaining the temperature for 2-4 hours ensures that the reaction proceeds fully, thus constructing a complete three-dimensional interpenetrating network of "rigid chain segment-flexible chain segment".
[0058] Example 8 This embodiment further explains the process parameters and feeding process in step 3, based on embodiment 7.
[0059] In step 3, after cooling to ≤60℃, refined silica powder, glass powder and fumed silica thixotropic agent are added, and the mixture is dispersed at high speed for 1-2 hours under vacuum conditions of -0.09~-0.1MPa. Then, defoamer and silane coupling agent are added, and the mixture is stirred under vacuum for 30-60 minutes to obtain component A.
[0060] As an example, the organosilicon in-situ grafted toughened epoxy resin obtained in step 1 was cooled to 60°C, and GPTMS surface-modified microsilica powder, refined silicon micro powder, glass powder, and fumed silica thixotropic agent were added. The mixture was then dispersed at high speed for 1.5 h under a vacuum of -0.095 MPa. Then, defoamer and silane coupling agent were added, and the mixture was stirred under vacuum for 45 min. After defoaming and uniformity, the mixture was discharged to obtain component A.
[0061] Therefore, cooling to ≤60℃ can avoid the impact of high temperature on the grafted organosilicon segments; high-speed dispersion under vacuum conditions ensures that the filler is uniformly dispersed in the epoxy matrix, avoiding agglomeration and sedimentation; defoamer and vacuum stirring further eliminate bubbles, ensuring that the colloid is dense and uniform.
[0062] Example 9 This embodiment further explains the process parameters and feeding process in step 4, based on embodiment 8.
[0063] In step 4, the temperature of the mixing reaction is 40-50℃, and the reaction is maintained at this temperature for 1-2 hours. Then, the accelerator and rheology modifier are added, and the mixture is stirred under vacuum for 30-60 minutes to obtain component B.
[0064] As an example, the modified amine curing agent was heated to 45°C, a biomimetic group modifier was added, and the reaction was maintained at this temperature for 1.5 hours. Then, an accelerator and a rheology modifier were added, and the mixture was stirred under vacuum for 30 minutes. The mixture was then discharged to obtain component B.
[0065] Therefore, it can be seen that within a temperature range of 40-50℃, the biomimetic group modifier can fully graft with the modified amine curing agent, and holding at this temperature for 1-2 hours ensures complete grafting; vacuum stirring eliminates air bubbles, ensuring the uniformity and storage stability of component B.
[0066] Example 10 This embodiment further explains the filling and molding process after step 5, based on embodiment 9.
[0067] In step 5, component A and component B are vacuum-filled into dual-gun tubes or barrels, respectively, and then mixed with a static mixer to obtain the finished building structural adhesive.
[0068] When using, component A and component B are mixed on-site at a mass ratio of 3:1 using a dual-gun and static mixer.
[0069] Therefore, vacuum filling can further prevent air from mixing in and ensure the compactness of the colloid; the dual-gun support with static mixer facilitates on-site mixing according to proportions and is suitable for various building structure reinforcement and repair scenarios such as rebar installation, steel bonding, prefabricated splicing, and joint sealing.
[0070] The general properties of the water-resistant, ultra-high toughness structural adhesive prepared by this invention are shown in Table 1 (meeting GB50728-2011 Class A): Splitting tensile strength ≥14MPa compressive strength ≥85MPa flexural strength ≥60MPa (non-fracture failure) Steel-to-steel tensile shear strength ≥16MPa Reinforcement / concrete bond strength ≥14MPa T-impact peel length 0mm Wet bond tensile strength (C45 concrete) ≥5MPa Table 1 Comparative Example 1 This comparative example provides a conventional structural adhesive for building construction that is neither toughened nor modified. Its formulation is as follows: 100 parts of bisphenol A type epoxy resin E51, 20 parts of unmodified microsilica powder, 38 parts of refined silica powder, 15 parts of glass powder, 4 parts of fumed silica thixotropic agent, and 48 parts of ordinary modified amine curing agent. No organosilicon toughening, GPTMS surface modification, or biomimetic group grafting modification is performed during the preparation process; conventional stirring technology is used.
[0071] Comparative Example 2 This comparative example provides a structural adhesive that is toughened but not surface modified or biomimetic grafted. Its formulation is as follows: 100 parts bisphenol A type epoxy resin E51, 10 parts organosilicon toughening agent, 20 parts unmodified microsilica powder, 38 parts refined silica powder, 15 parts glass powder, 4 parts fumed silica thixotropic agent, and 48 parts ordinary modified amine curing agent. During preparation, only in-situ organosilicon grafting toughening is performed; GPTMS surface modification and biomimetic group grafting modification are not performed.
[0072] The performance test data for Comparative Example 1 and Comparative Example 2 are shown in Table 2: Tensile shear strength 7.9-9.6MPa 10.2-12.5MPa ≥16MPa Wet bond strength 1-2MPa 2-3MPa ≥5MPa Storage status Easy to layer, easy to flow on the facade Slight stratification No layering, no flowing facade Cured state It is brittle and prone to interface damage. Improved resilience, but weaker interfacial bonding. Tough fracture, strong interfacial bonding Table 2 Therefore, it can be seen that the present invention, through the synergistic combination of in-situ grafting toughening of organosilicon, surface-modified microsilica powder of GPTMS, biomimetic group grafted modified amine curing agent and vacuum negative pressure preparation process, is significantly superior to the unmodified conventional solution in terms of tensile shear strength, wet bonding strength, storage stability and toughness.
[0073] In summary, this invention provides a method for preparing a water-resistant, ultra-high toughness structural adhesive, comprising the following steps: Step 1, mixing and reacting bisphenol A type epoxy resin with an organosilicon toughening agent at 60-80℃, maintaining the reaction temperature for 2-4 hours to obtain an organosilicon in-situ grafted toughening epoxy resin. Step 2, performing surface grafting modification treatment on microsilica powder and GPTMS to obtain GPTMS surface-modified microsilica powder. Step 3, cooling the organosilicon in-situ grafted toughening epoxy resin obtained in Step 1 to ≤60℃, adding the GPTMS surface-modified microsilica powder obtained in Step 2, refined silica powder, glass powder, and fumed silica thixotropic agent, and dispersing at high speed under vacuum conditions of -0.09~-0.1MPa for 1-2 hours, then adding an antifoaming agent and a silane coupling agent, and stirring under vacuum for 30-60 minutes to obtain component A. Step 4: Mix the modified amine curing agent and the biomimetic group modifier at 40-50℃ and maintain the reaction temperature for 1-2 hours. Then add the accelerator and rheology modifier, and stir under vacuum for 30-60 minutes to obtain component B. Step 5: Vacuum fill the components A obtained in Step 3 and B obtained in Step 4 into dual-tube dispensers or drums, respectively, and use a static mixer. The mass ratio of component A to component B is 2:1 to 4:1. After Step 5, vacuum fill the components A and B into dual-tube dispensers or drums, respectively, and use a static mixer.
[0074] The preferred embodiments disclosed above are merely illustrative of this specification. Optional embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the embodiments described herein. These embodiments are selected and specifically described in this specification to better explain the principles and practical applications of the embodiments, thereby enabling those skilled in the art to better understand and utilize this specification. This specification is limited only by the claims and their full scope and equivalents.
Claims
1. A water-resistant, ultra-high toughness structural adhesive for buildings, characterized in that, The structural adhesive is a two-component system, including component A and component B. Component A includes silicone in-situ grafted toughened epoxy resin and GPTMS surface-modified microsilica powder. Component B includes biomimetic group grafted modified amine curing agent. The mass ratio of component A to component B is 2:1 to 4:
1.
2. The water-resistant, ultra-high toughness structural adhesive according to claim 1, characterized in that, The in-situ grafted toughened epoxy resin is prepared by in-situ grafting of epoxy resin and silicone toughening agent. The silicone toughening agent is inserted in-situ into epoxy resin molecular chain segments to construct a three-dimensional interpenetrating network of rigid chain segments and flexible chain segments. The GPTMS surface-modified microsilica powder is prepared by grafting microsilica powder onto the GPTMS surface. The GPTMS introduces epoxy and hydroxyl groups on the surface of the microsilica powder, enabling covalent bonding between the microsilica powder, the epoxy matrix, and the curing agent. The biomimetic group grafted modified amine curing agent is prepared by grafting a modified amine curing agent and a biomimetic group modifier. The biomimetic group modifier mimics the active groups in marine biological adhesion proteins, covalently grafting biomimetic molecules containing amino or hydroxyl groups onto the epoxy backbone or side chains through a ring-opening reaction. This allows the curing agent to form hydrogen bonds, coordination bonds, and chemical crosslinks in humid or underwater environments, achieving efficient adhesion on wet surfaces and stable underwater curing.
3. The water-resistant, ultra-high toughness structural adhesive according to claim 2, characterized in that, The organosilicon toughening agent is made from 1,3-bis[3-(2,3-epoxypropoxy)-propyl]-1,1,3,3-tetramethyldisiloxane and dimethylcyclosiloxane.
4. The water-resistant, ultra-high toughness structural adhesive according to claim 2, characterized in that, The epoxy resin is a bisphenol A type epoxy resin; the modified amine curing agent is at least one of modified cycloaliphatic amine and polyether amine curing agent.
5. The water-resistant, ultra-high toughness structural adhesive according to claim 4, characterized in that, Component A further includes refined silica powder, glass powder, fumed silica thixotropic agent, defoamer, and silane coupling agent; Component B further includes accelerator and rheology modifier.
6. The water-resistant, ultra-high toughness structural adhesive according to claim 5, characterized in that, By weight, component A comprises: 100 parts bisphenol A epoxy resin, 8-12 parts organosilicon toughening agent, 15-25 parts GPTMS surface-modified microsilica powder, 30-45 parts refined silica powder, 10-20 parts glass powder, and 3-6 parts fumed silica thixotropic agent; component B comprises: 40-55 parts modified amine curing agent, 5-10 parts biomimetic group modifier, and 1-2 parts accelerator.
7. A method for preparing the water-resistant, ultra-high toughness structural adhesive as described in claim 6, characterized in that, Includes the following steps: Step 1: Mix epoxy resin and organosilicon toughening agent and react them at a temperature of 60-80℃ for 2-4 hours to obtain organosilicon in-situ grafted toughened epoxy resin. Step 2: Surface grafting modification treatment of microsilica powder and GPTMS is carried out to obtain GPTMS surface-modified microsilica powder; Step 3: Mix the in-situ grafted toughened epoxy resin obtained in Step 1 with the surface-modified microsilica powder of GPTMS obtained in Step 2 and other additives, and then perform vacuum degassing treatment to obtain Component A. Step 4: The modified amine curing agent and the biomimetic group modifier are mixed and reacted to obtain the biomimetic group grafted modified amine curing agent. Then, the additives are added and the mixture is subjected to vacuum stirring to obtain component B. Step 5: Vacuum fill the components A obtained in Step 3 and B obtained in Step 4 into dual-tube dispensers or drums, respectively, and use a static mixer. The mass ratio of component A to component B is 2:1 to 4:
1.
8. The method for preparing the water-resistant ultra-high toughness structural adhesive according to claim 7, characterized in that, In step 3, after cooling to ≤60℃, refined silicon micro powder, glass powder and fumed silica thixotropic agent are added, and dispersed at high speed for 1-2 hours under vacuum conditions of -0.09~-0.1MPa. Then, defoamer and silane coupling agent are added, and the mixture is stirred under vacuum for 30-60 minutes to obtain component A.
9. The method for preparing the water-resistant ultra-high toughness structural adhesive according to claim 8, characterized in that, In step 4, the temperature of the mixing reaction is 40-50℃, and the reaction is kept at this temperature for 1-2 hours. Then, an accelerator and a rheology modifier are added, and the mixture is stirred under vacuum for 30-60 minutes to obtain component B.